2017
DOI: 10.18006/2017.5(4).476.482
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bio-fertilizer on guava (Psidium guajava L.) cultivation in gangetic alluvial plain of West Bengal, India

Abstract: A field experiment was conducted at the farmer's field, Gayeshpur, Nadia, West Bengal during 2013-15 to study the effect of different bio-fertilizers on yield, fruit quality and leaf mineral composition of guava cv. L-49. The experiment was implemented using a randomized complete-block design with three replicates. Ten treatments of different bio-fertilizers alone and in combinations along with one chemical and absolute control i.e. no fertilization treatment were applied on 6 years old guava plant. Among diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
3
5
1
3
Order By: Relevance
“…On the other hand, the greatest guava plant growth obtained from seeds and inoculated with different species and the arbuscular mycorrhizal fungus combination has been reported previously (Estrada-Luna et al, 2000;Schiavo and Martins, 2002;da Silva-Campos et al, 2013;Mohandas et al, 2013;Das et al, 2017). In general, this study found an increase in guava plants propagated by seeds when a mycorrhizal consortium was applied.…”
Section: Guava Plant Growthsupporting
confidence: 66%
See 4 more Smart Citations
“…On the other hand, the greatest guava plant growth obtained from seeds and inoculated with different species and the arbuscular mycorrhizal fungus combination has been reported previously (Estrada-Luna et al, 2000;Schiavo and Martins, 2002;da Silva-Campos et al, 2013;Mohandas et al, 2013;Das et al, 2017). In general, this study found an increase in guava plants propagated by seeds when a mycorrhizal consortium was applied.…”
Section: Guava Plant Growthsupporting
confidence: 66%
“…Por otro lado, el mayor crecimiento de plantas de guayaba obtenidas de semilla e inoculadas con diferentes especies y combinaciones de HMA ya ha sido reportada previamente (Estrada-Luna et al, 2000;Schiavo y Martins, 2002;da Silva-Campos et al, 2013;Mohandas et al, 2013;Das et al, 2017). En general, en este trabajo se encontró un aumento en el crecimiento de las plantas de guayaba propagadas por semilla cuando se les aplicó algún consorcio micorrízico.…”
Section: Guava Plant Growthunclassified
See 3 more Smart Citations